The Role of Customer Relationship Management (CRM) in Increasing Customer Loyalty on E-Commerce Platforms in Indonesia - Ismi Mufida; Theodorus Sendjaja (Journal Social Society, 2026)
The urgency of research on the Role of Customer Relationship Management (CRM) in Increasing Customer Loyalty on E-Commerce Platforms in Indonesia is critical amid the sector's explosive growth CRM software market projected at USD 185 million in 2025 with 11.2% CAGR to USD 315 million by 2030 and churn rates over 30%, where effective CRM via personalization and two-way communication boosts loyalty by up to 40%. This descriptive qualitative study employs a systematic literature review methodology, selecting sources from 2018-2025 via Google Scholar, Scopus, Sinta-indexed journals, and industry reports like Statista and Mordor Intelligence, with criteria prioritizing empirical studies on Indonesian e-commerce CRM (e.g., Tokopedia, Shopee) focusing on loyalty metrics such as repeat purchases, retention rates, and path coefficients like 0.62 linking CRM to loyalty. Data collection involves gathering peer-reviewed articles, books, and reports on CRM dimensions operational (automation), analytical (predictive modeling), and strategic (cultural integration) while excluding pre-2018 or non-localized works. Analysis entails thematic coding to identify patterns, such as post-sale service enhancing repeat buys amid 200M+ internet users, classifying data into categories like personalization (strongest influencer), communication channels, and omnichannel strategies, then synthesizing connections via cross-study comparisons. Rigor is maintained through credibility (expert member checking and triangulation across 50+ sources), transferability (contextualized to SMEs driving 58% market via cloud CRM), dependability (detailed audit trails of selection), and confirmability (reflexive researcher notes on bias). Key findings highlight CRM's 20-40% loyalty uplift through AI-driven personalization post-pandemic, addressing gaps in SME adoption and localized e-commerce tactics for sustained revenue in a hyper-competitive market.